Adherence to antiretroviral therapy and its determinants among persons living with HIV/AIDS in Bayelsa state, Nigeria - Suleiman IA; Momo A (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: A high level of adherence is required to achieve the desired outcomes of antiretroviral therapy. There is paucity of information about adherence to combined antiretroviral therapy in Bayelsa State of southern Nigeria. Objectives: The objectives of the study were to determine the level of adherence to combined antiretroviral therapy among the patients, evaluate the improvement in their immune status and identify reasons for sub-optimal adherence to therapy. Methods: The cross-sectional study involved administration of an adapted and pretested questionnaire to 601 consented patients attending the two tertiary health institutions in Bayesla State, Nigeria: The Federal Medical Centre, Yenagoa and the Niger-Delta University Teaching Hospital Okolobiri. The tool was divided into various sections such as socio-demographic data, HIV knowledge and adherence to combined antiretroviral therapy. Information on the patient's CD4+ T cells count was retrieved from their medical records. Adherence was assessed by asking patients to recall their intake of prescribed doses in the last fourteen days and subjects who had 95-100% of the prescribed antiretroviral drugs were considered adherent. Results: Three hundred and forty eight (57.9%) of the subjects were females and 253 (42.1%) were males. The majority of them, 557 (92.7%) have good knowledge of HIV and combined anti-retroviral therapy with a score of 70.0% and above. A larger proportion of the respondents, 441 (73.4%), had ≥95% adherence. Some of the most important reasons giving for missing doses include, "simply forgot" 147 (24.5%), and "wanted to avoid the side-effects of drugs" 33(5.5%). There were remarkable improvements in the immune status of the subjects with an increment in the proportion of the subjects with CD4+ T cells count of greater than 350 cells/mm3 from 33 (5.5%) at therapy initiation to 338 (56.3%) at study period (p<0.0001). Conclusion: The adherence level of 73.4% was low which calls for intervention and improvement. The combined antiretroviral therapy has significantly improved the immune status of the majority of patients which must be sustained. "Simply forgot" was the most important reason for missing doses.